Absolute Gravity Network in Spain - Rodríguez Pujol, E. (Física de la Tierra, 2005)
Since the first absolute gravity measurements in Spain (in 1882 by Joaquín Barraquer y Rovira) no absolute measurements were performed till 1989 by J. Makinen, at the Institute of Astronomy and Geodesy of Madrid (IAG), with a Jilag-5 absolute gravimeter. BKG (Bundesamt für Kartographie und Geodäsie) of Germany and IMGC (Metrological Institute G. Colonetti) of Italy have measured six and three sites in Spain in the last decade of twentieth century. The National Geographic Institute of Spain (IGN) purchased the well known FG5 (num. 211) and A-10 (num. 006) absolute gravimeters. In order to have a reference of measurements to other absolute gravimeters three International Comparison of Absolute Gravimeters (ICAG) have been performed: ICAG2001 at the Bureau International des Poids et Mesures (BIPM) in Sèvres, ICSPAB03 at San Pablo de los Montes (Toledo, Spain) between European Center for Geodynamics and Seismology (ECGS) from Luxembourg and IGN from Spain and, finally, Walferdange 2003 International Intercomparison in Luxembourg. Not only absolute but also vertical gradient and relative measurements were also executed at every station for processing and datum reduction on the floor, because nominal height of absolute gravimeters is placed around 1.30 and 0.70 m above ground level. Results of Zero and a First order absolute gravity network will be presented, which hopefully will better the actual accuracies provided by the IGSN71 and RGFE73 and will serve for multidisciplinary purposes.